Intermediate cultural agents and the processes of updating in folkcommunication (Revista Internacional de Folkcomunicação, 2018)
My last face-to-face meeting with José Marques de Melo was in Recife / PE during FOLKCOM 2017, in which he made the important observation of the need to re-read Luiz Beltrão's studies to understand the media events in the 21st century in the context of folkcommunication. As I could not help being part of this commitment, I partially publish in this article the research I have been doing on popular traditional festivals and the importance of the new cultural intermediary agents in the processes of updating folk communication. Updates; Time; Heating; Marginalized; Cultural Hybrid.